1988
DOI: 10.3109/01674828809030947
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual cycle related complaints: A cross-cultural study

Abstract: Menstrual cycle related complaints: a cross-cultural study Menstrual and premenstrual complaints were compared amongst women from different ethnic groups in Australia, a country with a high immigrant population. One hundred and fifty-two women were asked to specify symptoms during the nienstrual cycle. Only 50.8% of women reported menstrual symptoms. The complaints were mostly somatic with a range of 37 to 73% between the different ethnic groups. Sixty-nine per cent reported suffering from premenstrualsymptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The mean length of menstrual cycle in Australian women was 29.2 ± 5.3 days. A set of data collected in 1988 indicated that the mean cycle length of Australian women was 27.7 days 17 . These data were based on a small sample size (25 subjects), however it suggests that Australian women have a shorter length of cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The mean length of menstrual cycle in Australian women was 29.2 ± 5.3 days. A set of data collected in 1988 indicated that the mean cycle length of Australian women was 27.7 days 17 . These data were based on a small sample size (25 subjects), however it suggests that Australian women have a shorter length of cycle.…”
Section: Discussionmentioning
confidence: 99%